REGULATION AND TRANSPARENCY OF THE FINANCIAL AUDIT OF EUROPEAN PROJECTS – A COMPARISON WITH STATUTORY AUDIT - Nina Adriana Buică; Marioara Avram; Magdalena Mihai; Cristian Drăgan (Annals of the University of Craiova: Economic Sciences Series, 2022)
Financial auditors, members of the recognized national professional bodies, provide independent services such as statutory audit of the annual financial statements published by economic entities and other financial audit services, out of which an important category is represented by the financial audit of projects financed through European funds. In this paper, we present a comparative study of the way these two activities are undertaken in Romania, from the point of view of the aspects concerning the regulatory and the transparency status of the audit services delivered. Following our analysis, we will present the common elements that have been identified between the two audit fields, the most important being the significant public interest presented by the audited information, the verification of the accounting of some complex economic transactions, the possibility of the appearance of errors and frauds in the process of the preparation and presentation of the audited information and the specific financial audit procedures that are applied by financial auditors in their audit work. Further, we will highlight the main differences existing between the two fields, respectively the legislative regulation as opposed to performing the audits based on the options of the management authorities or of the beneficiaries of the European funding, the different audit supervising bodies (ASPAAS - The Authority for Public Supervision of the Statutory Audit Activity and, respectively, CAFR - The Chamber of Financial Auditors of Romania) and the situation regarding the ensuring of the transparency of the audit activities performed. As a result of this research, we draw conclusions about the necessity and the means through which the financial audit of EU-funded projects can be better organized, monitored and exploited in order to support the protection of the financial interests of the European Union and implicitly of the European citizens.